If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 = 5(x + -4) + -1(x + -7) Reorder the terms: 11 = 5(-4 + x) + -1(x + -7) 11 = (-4 * 5 + x * 5) + -1(x + -7) 11 = (-20 + 5x) + -1(x + -7) Reorder the terms: 11 = -20 + 5x + -1(-7 + x) 11 = -20 + 5x + (-7 * -1 + x * -1) 11 = -20 + 5x + (7 + -1x) Reorder the terms: 11 = -20 + 7 + 5x + -1x Combine like terms: -20 + 7 = -13 11 = -13 + 5x + -1x Combine like terms: 5x + -1x = 4x 11 = -13 + 4x Solving 11 = -13 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 11 + -4x = -13 + 4x + -4x Combine like terms: 4x + -4x = 0 11 + -4x = -13 + 0 11 + -4x = -13 Add '-11' to each side of the equation. 11 + -11 + -4x = -13 + -11 Combine like terms: 11 + -11 = 0 0 + -4x = -13 + -11 -4x = -13 + -11 Combine like terms: -13 + -11 = -24 -4x = -24 Divide each side by '-4'. x = 6 Simplifying x = 6
| X=4(x+3)-6 | | b-1+7b=28 | | k/10=100 | | 0.1(x+60)-0.04(x-50)=5 | | 6(6x+7)=6 | | 24-2y=8y-7 | | -6a+24= | | 5+3=-4x+47 | | 6=6/10 | | 7y+12=3y-4 | | -4/3u-6=7/3u+8 | | -(4x-4)-(3x-5)+4=-9(x-1)-(2x+7)+3 | | -x-18= | | x+5-11=-3 | | (2v+9)(8-v)=0 | | 4x^3y+12x^2y-8xy= | | -(4x-4)-(3x-5)+5=-9(x-1)-(2x+7)+3 | | 6v+10=9v+9 | | 1+2x-x^2=0 | | 0.1(3.2+2x)+1/2(3-x/5)=0 | | 8x^3+18x^2-10x= | | X/31=17 | | -1.5-6x=26.7 | | 9/6=11/8 | | 3x+12-4= | | -1/3x=-5/6 | | 3(5x-2)=19 | | M-4-3m=-2m-3-1 | | (13x-6)-6(2x+2)=-6 | | 400+300/20 | | 0.5x+6=x+5/3 | | 2/x-2=-4/x+4+18/(x-2)(x+4) |